1980
DOI: 10.1097/00006123-198003000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Middle Cerebral Artery Fenestration

Abstract: Fenestration of the middle cerebral artery (MCA) is an unusual anomaly. We recognized and photographed MCA fenestration during an operation performed to clip an internal carotid artery aneurysm. The incidence of angiographic demonstration of this anomaly has been reported to be 0.26%. The clinical significance of fenestration of the vertebral and basilar arteries has primarily been the relationship of fenestration with other intracranial vascular anomalies. This is the first report of MCA fenestration associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Obvious MCA fenestration anomalies can be detected by magnetic resonance angiography, 18) but some small anomalies cannot be detected even by conventional angiography. 3,12) The incidence rates of MCA fenestrations detected by conventional angiography and autopsy are 0.17-0.43% 4,7,17) and 0.28-1%, 1,20) respectively. These variations can be attributed to the deficiencies of angiography, which may occasionally visualize fenestrated vessels as superimposed vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obvious MCA fenestration anomalies can be detected by magnetic resonance angiography, 18) but some small anomalies cannot be detected even by conventional angiography. 3,12) The incidence rates of MCA fenestrations detected by conventional angiography and autopsy are 0.17-0.43% 4,7,17) and 0.28-1%, 1,20) respectively. These variations can be attributed to the deficiencies of angiography, which may occasionally visualize fenestrated vessels as superimposed vessels.…”
Section: Discussionmentioning
confidence: 99%
“…An autopsy revealed that no perforators emerged from a fenestrated artery. 20) In another study, 12) intraoperative observation of the MCA fenestration accompanied by a ruptured internal carotidposterior communicating artery aneurysm revealed that the fenestration existed proximal to the lenticulostriate artery.…”
mentioning
confidence: 96%
“…Most of previous articles on the MCA fenestration focused on the association of cerebral aneurysm located at the site of fenestration or distant site from it. In the review of previous reports, 19 cases were coincided with cerebral aneurysms 1,5,7,[12][13][14][15][16][17][18][19]24,29,30,33) and 6 cases of aneurysm developed at the proximal or distal end of fenestration 5,12,18,19,24,30) . Other data indicated that the MCA fenestration was developed mainly at the M1 portion and there was no ethnic predilection between Asian and Western countries.…”
Section: Discussionmentioning
confidence: 99%